Subordinasi Perempuan: Rekonstruksi Peran Perempuan Dalam Pemilihan Umum di Indonesia - Kurniawati, Eka; Samhati, Siti (Universitas Islam Negeri Raden Intan Lampung, 2021)
Women's subordination has an impact on political life in Indonesia which is related to the impacts of gender discrimination, namely marginalization of stereotypes and excessive workload. From a methodological point of view, this article will be based on a case study, where the case is used as data showing gender inequality and even gender inequality, to then be analyzed based on a gender justice mechanism. in the positi district Spreading out domestic responsibilities between men and women, as well as increasing the insight of rural women through education will change the number of women who play a role in both the social conomic and poliltic fields will be more in tthe future.Keywords: Subordination, Women, Reconistrustion, General Election